Iron-Modified Biochar Strengthens Simazine Adsorption and Decreases Simazine Decomposition in the Soil - Cheng, Hongguang; Xing, Dan; Lin, Shan; Deng, Zhaoxia; Wang, Xi; Ning, Wenjing; Hill, Paul W.; Chadwick, David R.; Jones, Davey L. (Frontiers in Microbiology, 2022)
Currently, modified biochar has been successfully used in the remediation of soil polluted with heavy metals. However, the effects of the modified biochar on pesticides (such as simazine) are still unclear. Herein, the environmental fate of simazine, such as decomposition, leaching, and adsorption in unamended soil, in the soil amended with unmodified and modified biochar (biochar + FeCl3, biochar + FeOS, biochar + Fe) were evaluated. In addition, an incubation experiment was also performed to observe the influence of modified biochar on the microbial community and diversity in the soil. The results showed that modified biochar significantly decreased the decomposition of simazine in soil compared to its counterpart. Modified biochar also reduced the concentration of simazine in the leachate. Compared with the control, soil microbial biomass in the soil amended with unmodified biochar, biochar + FeCl3, biochar + Fe, and biochar + FeOS was decreased by 5.3%, 18.8%, 8.7%, and 18.1%, respectively. Furthermore, modified biochar changed the structure of the microbial community. This shows that modified biochar could increase the soil adsorption capacity for simazine and change the amount and microbial community that regulates the fate of simazine in the soil. This study concludes that iron-modified biochar has positive and negative effects on the soil. Therefore, its advantages and side effects should be considered before applying it to the soil.